Hadith Desimination Media - Rois Hamid Siregar; Rahmi Syahriza; Asrar Mabrur Faza (Penerbit Hellow Pustaka, 2025)
Hadith dissemination media plays a very important role in the spread and understanding of Islamic teachings in the digital era. Hadith, as the second source of Islamic teachings after the Qur'an, contains the words, deeds and approvals of the Prophet Muhammad SAW which guide the lives of Muslims. In the context of the development of information technology, the use of various digital media for the dissemination of hadith allows wider and faster access to Muslims throughout the world. Various platforms such as websites, mobile applications, social media, podcasts and learning videos are now effective means of disseminating hadith, not only in text form but also with explanations, interpretations and interactions that are easier to understand. This research aims to analyze various media products used in the dissemination of hadith and their benefits in expanding public understanding of the teachings of the Prophet Muhammad SAW. Apart from that, this journal also discusses the challenges faced in maintaining the authenticity of hadith amidst the rapid flow of digital information. The research results show that the medium of hadith dissemination in the digital era is very helpful in preserving Islamic teachings, increasing understanding of Muslims, and overcoming the spread of false hadith. However, selectivity in selecting valid sources of information remains very important in maintaining the quality of hadith dissemination.